Research education in an undergraduate curriculum: Students perspective - Alsuhaibani, Marya; Alharbi, Amjad; Inam, S. N. Bazmi; Alamro, Ahmad; Saqr, Mohammed (International Journal of Health Sciences, 2019)
Objective: This study aims to investigate the attitude and practice toward undergraduate research studies among medical students at Qassim University in Buraydah, Saudi Arabia. Methods: An online cross-sectional survey developed based on previous studies. It was announced to all registered medical students who have active college’s email (n = 448) at Qassim University in Buraydah, Saudi Arabia during the academic year of 2016. Results: The response rate was 56.6% (n = 252). Less than half of the students have started their research projects (41.6%). Students complained about the lack of free time and the unavailability of a university hospital: 92.4% and 97.1%, respectively. One-third of students participated in extra-curriculum research, and female students were more involved. Only 15.2% have published their research and 26.7% have presented it in conferences. Male students have more journal publication in compared to their female collages while the females have presented their projects more often in conferences. To improve their curriculum vitae, 95.2% stated they are going to participate in extra-curriculum research in the future. Conclusions: Students believe in the importance of research for improving their future work life. The main reason for not participating in research, beyond deficiency of research activities, is lack of free time. Students are unsatisfied with research skills gained through academic life, although their interest toward research increases and they plan on participating in future research.